A Statistical Examination of EMIC Wave‐Driven Electron Pitch Angle Scattering Signatures. Issue 2 (22nd February 2022) - Adair, L.; Angelopoulos, V.; Sibeck, D.; Zhang, X.‐J.
Abstract: Electromagnetic ion cyclotron (EMIC) waves have long been thought to contribute significantly to the variability of Earth's outer radiation belt because of their ability to scatter relativistic (>0.5 MeV) electrons into the loss cone on short timescales. We investigate statistically such pitch angle scattering signatures ("bite‐outs") and their quantitative agreement with cold plasma theory. Our analysis is based on EMIC wave events and local plasma parameters observed simultaneously with energetic electrons by the Van Allen Probes between February and May 2017. We determine the energy and pitch angle ranges in which relativistic electron scattering is likely and find that, on average, EMIC wave‐driven scattering of core ( E ≤ 2 MeV) electrons is possible in 28% of events. By comparing the expected ranges for scattering to electron flux measurements co‐located with the wave activity, we determine that scattering signatures are found in 46% of those. Additionally, we find that the scattering signatures are more likely to occur under increased geomagnetic activity and for waves with greater wave power. These results provide observational evidence that EMIC wave‐driven scattering of core relativistic electrons is common in the duskside outer radiation belt. Key Points: The minimum resonant energy of electrons falls below 2.0 MeV in ∼28% of EMIC wave events surveyed Approximately 46% of events were co‐located with relativistic electron pitch angle scattering signatures The presence of scattering signatures is dependent on geomagnetic activity and wave power